메타세콰이어나무 열매와 잎의 영양성분 및 항산화 활성 - 배영일(Young-Il Bae); 이주원(Ju-Won Lee); 하태정(Tae Jung Ha); 황승하(Seung-Ha Hwang); 신창식(Chang-Sik Shin); 정창호(Chang-Ho Jeong); 김일훈(Il-Hun Kim); 심기환(Ki-Hwan Shim) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2013)
The nutrients and antioxidative activities of fruits and leaves from Metasequoia glyptostroboides were investigated to provide basic data for the future development of functional foods. The nitrogen-free extract contents of fruit and leaves were 69.04% and 50.47%, respectively. Total phenolic content was higher in leaves (21.75 mg/GAE g) compared to the fruit (19.95 mg/GAE g). The mineral components of fruit and leaves mainly consisted of calcium (2,136.08 and 304.85 mg/100 g, respectively), potassium (1,355.53 and 1,144.04 mg/100 g, respectively), and phosphorous (426.30 and 350.50 mg/100 g, respectively). In terms of amino acid composition, aspartic acid, glutamic acid, proline, and leucine were relatively high, but methionine and cystine were low. The hot water extract from leaves was a more potent free radical-scavenger and had higher reducing activities than extracts from fruit. Thus, phenolics of M. glyptostroboides leaves can be utilized as an effective functional food substance for its natural antioxidant properties. 메타세콰이어 나무 열매와 잎을 기능성식품 소재로 활용하기 위한 기초자료를 제공하기 위하여 화학성분 및 항산화 활성을 조사하였다. 열매와 잎의 가용성 무질소물의 함량은 각각 69.04% 및 50.47%로 나타났으며, 열매의 총 페놀성 화합물 함량은 19.95 mg/GAE g이었고, 잎의 총 페놀성 화합물의 함량은 21.75 mg/GAE g으로 열매보다 잎에서 높은 함량을 보였다. 열매와 잎에 많이 함유되어 있는 무기성분으로는 Ca(2,136.08와 304.85 mg/100 g), K(1,355.53와 1,144.04 mg/100 g) 및 P(426.30와 350.50 mg/100 g)이었다. 아미노산은 aspartic acid, glutamic acid 및 proline이 상대적으로 높았으며, 필수아미노산 중에서는 leucine이 상대적으로 높은 비율을 보였고, methionine과 cystine은 낮은 함량을 보였다. 메타세콰이어 열매와 잎의 열수 추출물을 이용하여 라디칼 소거활성 및 환원력을 조사한 결과 농도 의존적인 경향을 보였으며, 특히 잎 열수 추출물에서 높은 항산화 활성을 보였다. 따라서 메타세콰이어나무 잎의 폴리페놀성 화합물은 천연항산화제와 같은 기능성식품 소재로 활용가능성이 매우 높을 것으로 생각된다.